Gentle care for baby skin - N. M. Sharova (Медицинский совет, 2016)
The article is devoted to the anatomical and physiological characteristics of the skin of babies and new options for gentle care. Some results of preclinical and clinical studies of skin care with Realba® oat extract are demonstrated.